Subjective Well-Being and Income: Is there any Evidence of Satiation? - Betsey Stevenson; Justin Wolfers (Center for Economic Studies and ifo Institute (CESifo), 2013)
Many scholars have argued that once basic needs have been met, higher income is no longer associated with higher in subjective well-being. We assess the validity of this claim in comparisons of both rich and poor countries, and also of rich and poor people within a country. Analyzing multiple datasets, multiple definitions of basic needs and multiple questions about well-being, we find no support for this claim. The relationship between well-being and income is roughly linear-log and does not diminish as incomes rise. If there is a satiation point, we are yet to reach it.
Keywords: D60; I30; N30; O10; O40; 330; subjective well-being; happiness; satiation; basic needs; Easterlin paradox